THE HOLOCAUST TRAGEDY AND JEWISH SITES OF MEMORY IN UKRAINE IN THE NOVEL EVERYTHING IS ILLUMINATED BY J. S. FOER - Siekierska, Marta (Porównania, 2019)
Marta Siekierska, THE HOLOCAUST TRAGEDY AND JEWISH SITES OF MEMORY IN UKRAINE IN THE NOVEL EVERYTHING IS ILLUMINATED BY J. S. FOER. “PORÓWNANIA” 1 (24), 2019. Vol. XXIV, P. 135-145. ISSN 1733-165X. The aim of this paper is to analyze the novel Everything is illuminated by Jonathan Safran Foer with consideration of the relation of the form and language to historical trauma experienced by the hero of this novel. The distinctive form and language employed by the author account for an innovative restatement of the history and the theme of extermination. The paper also addresses the landscape of the Ukrainian-Polish borderline, in Foer’s work portrayed as one marked by historical, metaphysical and cultural borders. The subsequent object of analysis is the rich symbolism of Everything is illuminated which accentuates the sense of meaningful absence, the blank space of memory that remains after the annihilation of the Jewish community.